Land use and biotic integrity in shallow streams of the Hondo River basin, Yucatan Peninsula, Mexico - Pacheco-Díaz, Rodrigo I. (2017)
Aquatic environments face a variety of threats in the Hondo River basin, Southeastern Yucatan Peninsula. Some of these impacts, like pollution by pesticides, may depend on land use and cover. Our objective was to assess the effect of land use/cover using a previously published index of biotic integrity (IBI), based on fishes and designed for shallow streams in the Hondo River basin. Our hypothesis was that land uses that cause deforestation and pollution, such as urbanization, cattle breeding, or sugar cane fields, would be reflected in low IBI values, at least at some spatial scales. The 23 sites originally used in 2008-2009 to estimate by electrofishing the relative abundance and other characteristics of selected fish species and guilds to construct the IBI, were revisited in February 2010, to validate by direct inspection the type of land use/cover suggested by landscape information in digital databases. We analyzed the effect of seven types of land use/cover (agriculture, pasture, human settlements, water bodies, wetlands, forest, and secondary vegetation) on the IBI values, at four spatial scales, i.e., the percent of every land use/cover at progressively larger circles (125, 250, 500, and 1 000 m diameter) centered on the water body where the IBI value was measured. Correlations were established among the percent land/use cover by scale around 23 sites, and with their corresponding IBI values. Then, Student’s t tests were calculated to examine significant differences in land use/cover between groups of localities above and below the median IBI value, and Mann-Whitney’s U tests were applied to compare IBI values between localities with and without a given landscape cover. Agriculture, human settlements, and secondary vegetation correlated negatively with the IBI; forests positively.  Differences were significant (p < 0.05) for forest (higher in sites with higher IBI values) and human settlements (lower in sites with higher IBI). Of all the landscape categories located in the Hondo River basin, with the exception of pasture, those of anthropogenic origin tended to be detrimental to aquatic biotic integrity.